Incorporation of a minimal nucleotide into DNA. Issue 48 (28th November 2018) - Röthlisberger, Pascal; Levi-Acobas, Fabienne; Sarac, Ivo; Ricoux, Rémy; Mahy, Jean-Pierre; Herdewijn, Piet; Marlière, Philippe; Hollenstein, Marcel
Graphical abstract: Highlights: Synthesis of an abasic site triphosphate dФTP was achieved using a hydrocynnamoyl protecting group strategy. dФTP can be incorporated into DNA by polymerases. The incorporation is best when dA is the templating nucleotide. dФTP can be incorporated opposite abasic sites. Abstract: Abasic sites are amongst the most frequent DNA lesions and result from spontaneous hydrolysis of the glycosidic bond or from the removal of damaged nucleobases. These depurination events can also occur on free deoxyribonucleoside triphosphates present in cells and lead to the formation of an abasic site triphosphate of which very little is known. Herein, we report the synthesis and biochemical characterization of the minimal triphosphate dФTP. Unexpectedly, dФTP is tolerated by various DNA polymerases and the incorporation efficiency obeys the A-rule. Single incorporation of dФMP units were also observed opposite abasic sites and the addition of prosthetic molecules mimicking base-pairs do not seem to favor the process.